A color graphic informing on the impact of electric lighting and coated glazing in complex architectural scenes. Issue 6 (8th September 2018) - Cauwerts, Coralie; Jost, Sophie
Abstract: The present work proposes a graphical indicator that provides descriptive information about the color content of architectural environments, and shows color shifts due to illuminant or glazing changes. This color graphic is in accord with representations recently developed in electric lighting to provide information on color rendering. Its originality lies in (1) including contextualization, (2) dividing the color space based on color naming, and (3) giving the user the opportunity to compare scenes with different correlated color temperatures. After describing the development steps of the color graphic, two case studies and three validation experiments are presented. While the application of the graphic highlights its interest in a building design process, the validation experiments identified potential improvements.